68.2k views
1 vote

simplify

(3 + 4 √(5))(2 - x √(5)) = 2 √(5) - 34


User Stephen K
by
5.9k points

1 Answer

0 votes

Answer:

x = 2

Explanation:

Given


(3+4√(5))(2-x√(5))=2√(5)-34

First, open the brackets using distributive property:


(3+4√(5))(2-x√(5))\\ \\=3(2-x√(5))+4√(5)(2-x√(5))\\ \\=6-3x√(5)+8√(5)-4√(5)x√(5)\\ \\=6-3√(5)x+8√(5)-20x\ [\text{since} √(5)\cdot √(5)=5, \ \text{then }4√(5)\cdot √(5)=20]

Now, combine the like terms:


6-3√(5)x+8√(5)-20x\\ \\(6-20x)+√(5)(8-3x)

Since
(3+4√(5))(2-x√(5))=2√(5)-34, you have that


6-20x=-34\Rightarrow 20x=40,\ x=2\\ \\8-3x=2\Rightarrow 3x=6,\ x=2

User The Zero
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.